Inside the house of money : top hedge fund traders on profiting in the global markets - Drobny, Steven. (J. Wiley & Sons, 2006)
Inside the House of Money lifts the veil on the typically opaque world of hedge funds, offering a rare glimpse at how today's highest paid money managers approach their craft. Author Steven Drobny demystifies how these star traders make billions for well-heeled investors, revealing their theories, strategies and approaches to markets.